1968
DOI: 10.1083/jcb.36.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Studies on the Lymphatic Anchoring Filaments

Abstract: The fine structure of the lymphatic capillary and the surrounding tissue areas was investigated. Instead of a continuous basal lamina (basement membrane) surrounding the capillary wall, these observations revealed the occurrence of numerous fine filaments that insert on the outer leaflet of the trilaminar unit membrane of the lymphatic endothelium. These filaments appear as individual units, or they are aggregated into bundles that are disposed parallel to the long axis of the lymphatic capillary wall and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
159
0
2

Year Published

1969
1969
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(165 citation statements)
references
References 18 publications
4
159
0
2
Order By: Relevance
“…Lymphatic anchoring filaments (Leak and Burke, 1968) and suspensory ligament of the ocular lens (Raviola, 1971) are oxytalan fibers, or elastin-free MFs. Their roles not in elasticity but in architectural and mechanical stiffness has been emphasized (Ramirez and Pereira, 1999;Kielty et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic anchoring filaments (Leak and Burke, 1968) and suspensory ligament of the ocular lens (Raviola, 1971) are oxytalan fibers, or elastin-free MFs. Their roles not in elasticity but in architectural and mechanical stiffness has been emphasized (Ramirez and Pereira, 1999;Kielty et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…They appear to connect endothelial cells to elastic fibers in the subendothelial matrix of the mouse aorta [10] and of lymphatic capillaries [11,12]. In the mouse aortic media the elastic laminae are linked to smooth muscle cells by bundles of microfibrils [13].…”
Section: Introductionmentioning
confidence: 99%
“…This might suggest that microfibrils are found exclusively in the sites where elastogenesis should take place; however, it has been shown that fibrillin microfibrils devoid of amorphous elastin also occur in nonelastic, fully developed tissues. Oxytalan fibers in the periodontal ligament (Fullmer and Lillie, 1958;Carmichael and Fullmer, 1966), lymphatic anchoring filaments (Leak and Burke, 1968), and suspensory ciliary ligament of the ocular lens (Inoue and Leblond, 1986;Wright et al, 1994) form bundles of elastin-free microfibrils. A fibrillar system in the dermis is also known to contain elastin-free microfibrils in its superficial region (Cotta-Pereira et al, 1976, 1977.…”
mentioning
confidence: 99%